Subcritical water technology for extraction of phenolic compounds from Chlorella sp. microalgae and assessment on its antioxidant activity - Zakaria, Siti Maisurah; Mustapa Kamal, Siti Mazlina; Harun, Mohd Razif; Omar, Rozita; Siajam, Shamsul Izhar (MDPI, 2017)
Chlorella sp. microalgae is a potential source of antioxidants and natural bioactive compounds used in the food and pharmaceutical industries. In this study, a subcritical water (SW) technology was applied to determine the phenolic content and antioxidant activity of Chlorella sp. This study focused on maximizing the recovery of Chlorella sp. phenolic content and antioxidant activity measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay as a function of extraction temperature (100-250 °C), time (5-20 min) and microalgae concentration (5-20 wt. %) using response surface methodology. The optimal operating conditions for the extraction process were found to be 5 min at 163 °C with 20 wt. % microalgae concentration, which resulted in products with 58.73 mg gallic acid equivalent (GAE)/g phenolic content and 68.5% inhibition of the DPPH radical. Under optimized conditions, the experimental values were in close agreement with values predicted by the model. The phenolic content was highly correlated (R² = 0.935) with the antioxidant capacity. Results indicated that extraction by SW technology was effective and that Chlorella sp. could be a useful source of natural antioxidants.